THE IMPACT OF GREEN MARKETING STRATEGIES ON CONSUMERS’ PURCHASING INTENTION - Mushtariy Shaimova Karim qizi (Modern American Journals, 2025)
Green marketing has emerged as a significant strategy in the contemporary marketing landscape, driven primarily by growing global environmental concerns and increased consumer awareness about the ecological impact of products and services. Traditionally, marketing focused on product features and value; however, modern consumers increasingly demand that companies demonstrate environmental responsibility. Green marketing, therefore, involves promoting environmentally friendly products or corporate practices to appeal to this environmentally conscious consumer base (Ali, 2019). The shift towards sustainability is not only a regulatory and ethical imperative but also a competitive advantage, as statistics indicate that the global green marketing market is projected to grow extensively fueled by consumer demand for eco-friendly alternatives (Ashoush & Kortam, 2022).